The Politics of Mining and Religion: Argumentative Conflict Between Gusdurian and PBNU from the Perspective of Antonio Gramsci's Hegemony: Politik Tambang dan Agama: Konflik Argumentasi Antara Gusdurian dan PBNU dalam Perspektif Hegemoni Antonio Gramsci - Ilham Syamsul; Geri Septian; M. Muammar Kafani (Universitas Indo Global Mandiri, 2026)
Purpose: This study examines the argumentative conflict between the Nahdlatul Ulama Executive Board (PBNU) and the Gusdurian Network in the polemic over mining management policy through the perspective of Antonio Gramsci's hegemony, focusing on the use of religious authority, Islamic discourse, and institutional legitimacy as instruments of ideological contestation in the public sphere. Design/methodology/approach: The study employed a qualitative approach based on literature review and comparative studies. Data sources included official statements, published articles, and online media texts from both actors. The analysis was conducted in three stages: identification of argumentative positions, comparative paradigm analysis, and application of Gramsci's hegemony categories. Findings: PP No. 25 of 2024, Article 83A, represents a practice of ideological domination based on a development narrative. PBNU legitimizes mining through the discourse of the public good and Islamic jurisprudence, thus constructing a new common sense that aligns mining with Islamic values. Gusdurian challenges this through ecological critique and social justice arguments. Within Gramsci's framework, PBNU functions as a traditional intellectual group aligned with the state's hegemonic bloc, while Gusdurian operates as an organic intellectual group building an alternative historical bloc, a war of positions over the meaning of Islamic ethics and the public good. Practical Implication: This research encourages the public to be more critical of politically motivated religious narratives. Originality/value: This research's originality lies in the combination of Gramsci's hegemonic perspective with the dynamics of mining policy polemics in the context of Indonesian Islamic organizations. Paper type: Review Paper